FUZZY LOGIC AND SPATIAL ANALYSIS IN GIS ENVIRONMENT - Di Martino, Ferdinando; Sessa, Salvatore (BDC. Bollettino Del Centro Calza Bini, 2015)
In the context of the fuzzy logic we use a system of max-min fuzzy relation equations to solve a problem of spatial analysis in a Geographical Information Systems (GIS). The geographical area under study is divided in subzones to which we apply our process to determine the outputs after that an expert sets the whole SFRE with the values of the coefficients impacting the input data. We find the best solutions by associating the results to each subzone and thematic maps are extracted from the GIS. Keywords: system of max-min fuzzy relation equations, GIS, triangular fuzzy number